A Comparative Study of the Prevalence of Bl00d Gr0ups System and Rhesus Factor in a Sample of Donors from the Cities of Samawah and Rumaytha - Alfahad, Ahmed A. N. (American Journal of Bioscience and Clinical Integrity, 2026)
An analysis of the distribution pattern and prevalence of (ABO) blood group and (Rh) rhesus factor among the targetwas studied among 780 individuals in the cities of Samawah and Rumaitha. The findings of our study revealed that blood group O had the highest prevalence among both males and females, with 266 individuals (34.2%). In contrast, blood group AB showed the lowest prevalence, accounting for 62 individuals (7.9 %). Blood group A was observed in 246 individuals (31.5 %), while blood group B was identified in 206 individuals (26.4 %). Analysis of the distribution of Rh that O⁺ was the most common phenotype, observed in 246 individuals (31.5 %), whereas AB⁺ was the least common among Rh-positive groups, with 60 cases (7.7 %). Among Rh-negative phenotypes, O⁻ showed the highest proportion, with 19 individuals (2.4 %), while AB⁻ represented the lowest proportion, with 2 individuals (o.3 %). This research was undertaken to determine the patterns of distribution of the ABO and Rh blood group systems within the general population of Samawah and Rumaytha.